Reserve Requirements in Islamic Banking System: A Critical Survey - Satria Hibatal zizy (Islamic Economics Journal, 2012)
The discourse of westernization and liberalization had been spread to Muslim ummah nowadays. To decrease the impact of both problems, Muslim scholars seek for a solution called Islamization of knowledge. This effort took place in every sphere in human life, including economics, and specifially in banking sector. One concern in Islamization’s effort on banking sector is reserve requirements policy, which the muslim economists have different opinions on it, between imposing fractional reserve requirements or 100% reserve requirements. In case of reserve requirements, muslim economists are divided into two major groups. The fist, which represented by Umer Chapra, Nejatullah Siddiqi, MonzerKahf, Afzalurrahman and Mohamed Ariff, they saw that fractional reserve requirements is a right way for Islamic banking system. The reserve used for ensure bank’s ability to fulfil it obligation to the depositors. In addition, it could be used by Islamic central bank as a tool of monetary policy to control money supply. The second, represented by Mabid Ali AlJarhi, Mohsin S. Khan, Abbas Mirakhor and Mahmoud Abu Saud recommend the use of 100% reserve requirements. According to them, fractional reserve system could suffer such an inherent instability. Over expansion of credit is often occurring this system that imply to unstable infltion. Their assumption is 100% reserve requirements will bring to more stable economy.